Redesain sarana angkut barang untuk sepeda motor kurir online - Prakasa, Aldino Unggul; Wahmuda, Faza (Institut Seni Indonesia Yogyakarta, 2024)
Expedition services experienced an increase during the pandemic, this happened because during the pandemic people were encouraged to stay at home, but their daily needs must still be met. The increase in expedition services has a problem with motorbike couriers who are tasked with sending goods to consumers' homes, where the transportation means that the courier uses use materials that are not waterproof and also easily torn. From these problems, it is necessary to redesign the means of transporting goods that are resistant to various weathers. To solve this problem, the researcher uses the mix method, namely qualitative and quantitative research methods. Observations were made at two places in the city of Surabaya which were then used for work requirements analysis, storage needs analysis, ergonomics analysis, placement analysis, dimension analysis, material analysis, system analysis, shape analysis, colour analysis, and sign analysis. Then the design synthesis, design concepts, initial sketches, five alternative designs were obtained which were then distributed to motorcycle couriers to obtain the final design which was then closed with conclusions and suggestions. The result of the research is the redesign of the means of transporting goods which has two parts, namely the top and bottom using a jeep hood material and foam heart, some parts can be opened and closed using a zipper system, velcro, buckle, and reflective tape that can reflect light at night day.